2010
DOI: 10.1007/s10802-010-9480-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Response in CP/ADHD Children with Callous/Unemotional Traits

Abstract: The current study examines the role of callous/unemotional (CU) traits in response to treatment among children with conduct problems (CP) and attention-deficit/hyperactivity disorder (ADHD). Fifty-four children with CP/ADHD and 16 controls (age = 9.48, SD = 1.58) took part in a summer treatment and research program. Simple correlations showed that CU and CP were associated with a number of treatment outcome measures. When examined together in regression analyses, CU and CP were uniquely associated with three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 48 publications
7
106
1
6
Order By: Relevance
“…This interpretation is consistent with the findings of impaired social perception and problem-solving in aggressive children (Lochman and Dodge 1994). Despite the growing recognition of CU traits in children and adolescents with conduct disorder, little is known about their effect on treatment for aggression (Hawes and Dadds 2005;Haas et al 2011). We will evaluate whether the decreased amygdala response to fearful faces, as a biomarker of CU traits, predicts poorer response to CBT.…”
Section: Biomarkers Of Cu Traits As Predictors Of Response To Cbt Forsupporting
confidence: 85%
“…This interpretation is consistent with the findings of impaired social perception and problem-solving in aggressive children (Lochman and Dodge 1994). Despite the growing recognition of CU traits in children and adolescents with conduct disorder, little is known about their effect on treatment for aggression (Hawes and Dadds 2005;Haas et al 2011). We will evaluate whether the decreased amygdala response to fearful faces, as a biomarker of CU traits, predicts poorer response to CBT.…”
Section: Biomarkers Of Cu Traits As Predictors Of Response To Cbt Forsupporting
confidence: 85%
“…A similar finding appeared with C/U traits, which also predicted better D-Total response for both treatment groups. These data contribute to a mixed literature surrounding the treatment resistance of children with C/U traits, at least to behavioral intervention (e.g., Kolko and Pardini 2010;Haas et al 2011). However, it is important to note that the C/U composite used in this article was not a validated measure, and future research should employ existing measures such as the Antisocial Process Screening Device (Frick and Hare 2001).…”
Section: Predictorsmentioning
confidence: 80%
“…Of the studies about treatment that compared the outcome of treatment for youths with conduct problems with and without elevated levels of CU traits, most of the studies reported that the group high on CU traits showed poorer treatment outcomes and treatment noncompliance. Speciically, several studies of adolescents with higher psychopathic or CU traits were demonstrated that adolescents were less compliance in treatment and poorer institutional adjustment and were more likely to reofend after treatment [157,[160][161][162]. Similarly, in inpatient psychiatric setings, children (ages 7-11) with elevated levels of CU traits had longer length of stay and experienced more physically restrictive interventions during hospitalization [163].…”
Section: Treatmentmentioning
confidence: 99%
“…Similarly, in inpatient psychiatric setings, children (ages 7-11) with elevated levels of CU traits had longer length of stay and experienced more physically restrictive interventions during hospitalization [163]. In a school-aged sample of children enrolled in a summer treatment program for externalizing behavior problems, children with children conduct problems and CU traits responded less well to behavior therapy alone than children with conduct problems without CU traits [164] and less improvement in social skills and problem-solving skills when compared to children with CP alone [162]. Hawes and Dadds also found that boys with CU displayed lower treatment response to behavioral parent training and were particularly less responsive to time-outs [165].…”
Section: Treatmentmentioning
confidence: 99%